The Accessory Consequences and the Criminal Procedure Code 2004 - Prado Saldarriaga, Víctor Roberto (2008)
The criminal dimension of the legal people demands an effective and opportune social reaction with the same degrees of «desvalor», punishment and sanction applied to the physical people, for which the inclusion in the Criminal Procedure Code of 2004 of the accessory consequences applicable to the legal people in the penal process is extremely important. Keeping that in mind, a general vision of the doctrine on the subject is presented in the text, after which the Peruvian normativity regarding the procedural emplazamiento of the legal person it is studied, its incorporation in the process, the procedural rights and guarantees and the precautionary measures that can be applied to the legal people, among other subjects.